Attitudes, Decision Making and Purchasing Patterns of Online Vegetable Consumers - Talenta Priska Andini; Rabiatul Adawiyah; Yaktiworo Indriani (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2023)
The COVID-19 pandemic has changed consumer behavior; therefore, it is interesting to understand consumer behavior when purchasing vegetables online. This study aims to determine consumer attitudes, decision-making processes, and patterns in purchasing vegetables online at Bejana.id. The research location in Bandar Lampung City was purposively selected with the consideration that the company is representative for achieving research objectives. Sample determination was performed by the non-probability method with the quota sampling technique. There were 45 research samples consisting of 40 B2C consumers (individuals/households) and five B2B consumers (hotels, restaurants, and cafes). The data were collected from January to February 2023. The data were analyzed descriptively using the Fishbein Multi-attribute model. The results showed that the attitude of Bejana.id consumers was in the good category with the most preferred attributes, namely, the attributes of the expiration period inclusion (product component) and the accuracy of the product according to the order (service component). Consumers buy vegetables online through problem recognition, information search, alternative evaluation, purchase decisions, and post-purchase behavior. B2C consumers form a purchasing pattern with an amount of 2.1 bunches or 2.8 packs each week with the type of vegetables, namely leaf vegetables, which in one purchase reaches IDR 50,000.00 - IDR 100,000.00, with a frequency of once per week. The vegetables most purchased by B2B consumers are leaf vegetables, fruit vegetables, and root vegetables, which are routinely purchased 3-4 times each week with one purchase reaching IDR 1,000,000.00 - IDR 3,499,999.00.